AB0108 THE ROLE OF CD70 IN THE PATHOGENESIS OF RHEUMATOID ARTHRITIS. (June 2019) - Yoo, Su-Jin; Kang, Seong Wook; Kim, Jinhyun; Yoo, In Seol; Park, Chan Keol; Lee, Ha-Reum
Abstract : Background: Rheumatoid arthritis (RA) is characterized by inflammation and cellular proliferation in the synovium. Activated lymphocytes and proinflammatory molecules are important in the pathogenesis of RA. CD70 belongs to the tumor necrosis factor (TNF) ligand superfamily and is typically present on activated B and T lymphocytes, natural killer cells and mature dendritic cells. CD70 expressing CD4 + T cells are enriched in the peripheral blood and synovial fluid of patients with RA and promote autoimmunity via co-stimulatory CD70-CD27 interaction. CD70 expression is associated with aggressive phenotype of cancer cells and it is mediated by hypoxia inducible factor 2α (HIF-2α). Objectives: In this study, we examined the presence of CD70 on the surface of fibroblast-like synoviocyte (FLS) of patients with RA (RA-FLS) and investigate the role of CD70 in the pathogenesis of RA associated with HIF-2α. Methods: RA FLS were obtained from 7 patients with RA who were undergone operation like total knee replacement or synovectomy. All patients were fulfilled the 2010 ACR-EULAR classification criteria for RA. CD70 and HIF-2α messenger ribonucleic acid (mRNA) were analyzed in RA-FLS by quantitative polymerase chain reaction ( qPCR ). CD70 and CD27 on the surface of RA-FLS were stained by PE-Anti CD70 antibody and PerCP-Cy5.5-CD27 antibody respectively and evaluated by flow cytometry. Same experiments were performed after treatment with interleukin (IL)-17, TNF-α and HIF-2α blocking antibody (Anti HIF-2α antibody). Results: CD70 and HIF-2α mRNA in the RA-FLS were elevated after treatment with IL-17 and TNF-α (Figure 1, 2 ). The level of CD70 expression on the surface of RA-FLS was elevated after stimulation with IL-17 and TNF-α (Figure 3 ). And it was lowered after treatment with HIF-2α blocking antibody as dose dependent pattern (Figure 3 ). CD27 wasn't present on the surface of RA-FLS (Figure 4 ). Conclusion: We identified the expression of CD70 on the surface of RA-FLS. And in inflammatory conditions like stimuation with IL-17 and TNF-α, both CD70 and HIF-2α mRNA were increased. The level of CD70 on the surface of RA-FLS also elevated by treatment with IL-17 and TNF-α. The result of decreased level of CD70 after treatment with anti HIF-2α antibody suggest that CD70 expression on the surface of RA-FLS is associated with HIF-2α. From these results, we expect that CD70-targeted therapy associated with HIF-2α may be effective for treatment with RA. References: [1] Han, B. K., Olsen, N. J., & Bottaro, A. (2016). The CD27-CD70 pathway and pathogenesis of autoimmune disease. Semin Arthritis Rheum, 45(4), 496-501. [2] Kitajima, S., Lee, K. L., Fujioka, M., Sun, W., You, J., Chia, G. S. Poellinger, L.(2018). Hypoxia-inducible factor-2 alpha up-regulates CD70 under hypoxia and enhances anchorage-independent growth and aggressiveness in cancer cells. Oncotarget, 9(27), 19123-19135. [3] Lee, W. W., Yang, Z. Z., Li, G., Weyand, C. M., & Goronzy, J. J. (2007). Unchecked CD70 expression on T cells lowers threshold for T cell activation in rheumatoid arthritis. J Immunol, 179(4), 2609-2615. [4] Oflazoglu, E., Boursalian, T. E., Zeng, W., Edwards, A. C., Duniho, S., McEarchern, J. A. Grewal, I. S. (2009). Blocking of CD27-CD70 pathway by anti-CD70 antibody ameliorates joint disease in murine collagen-induced arthritis. J Immunol, 183(6), 3770-3777. [5] Park, J. K., Han, B. K., Park, J. A., Woo, Y. J., Kim, S. Y., Lee, E. Y., Song, Y. W. (2014). CD70-expressing CD4 T cells produce IFN-gamma and IL-17 in rheumatoid arthritis. Rheumatology (Oxford), 53(10), 1896-1900. [6] Ruf, M., Moch, H., & Schraml, P. (2015). Interaction of tumor cells with infiltrating lymphocytes via CD70 and CD27 in clear cell renal cell carcinoma. OncoImmunology, 4(12), e1049805. Disclosure of Interests: None declared